Assessment of sarcopenia in female patients with sarcoidosis upon initial diagnosis - Samancı, Cesur; Salt, Vefa; Demir, Bilal; Hamid, Rauf; Sarıahmetoğlu, Ömer Faruk; Acar, Kerime Hatun; Karagöz, Seyfullah Halit; Üstündağ, Ahmet; Çalışkaner Öztürk, Buket; Atahan, Ersan; Ateş Ustabaşoğlu, Fatma; Baş, Ahmet (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2026)
Background and aim: There is a substantial body of literature that discusses the potential relationship between sarcopenia and sarcoidosis. This study aimed to evaluate the muscle mass of sarcoidosis patients without any treatment at the time of diagnosis using computed tomography (CT) images.Methods: This retrospective study included only female patients, as the vast majority of sarcoidosis cases in our dataset were female, and this approach allowed us to minimize gender-related confounding. The sarcoidosis group consisted of newly diagnosed, untreated female patients who underwent abdominal CT as part of their diagnostic work-up. The control group comprised female patients with a comparable age distribution to the sarcoidosis cohort, who presented to the emergency department with non-chronic, unrelated conditions and had no history of chronic illness or medication use known to affect muscle mass. Total skeletal muscle (TSM), skeletal muscle index (SMI), and psoas muscle index (PMI) at the L3 vertebral level were measured using manual segmentation. SMI-based sex-, age-, and BMI-specific thresholds from the literature were used to define sarcopenia.Results: A total of 168 female patients were evaluated. Sarcoidosis patients were significantly older and shorter than controls. TPM (p = 0.003), TSM (p = 0.027), SMI (p = 0.037), and PMI (p = 0.001) values were significantly lower in the sarcoidosis group. However, the prevalence of sarcopenia based on SMI criteria did not significantly differ between groups. Notably, significant muscle mass differences were most evident in the 50–60 age group.Conclusions: Our findings suggest that muscle loss may already be present at the time of diagnosis in female sarcoidosis patients, becoming more apparent with age. Further studies with broader populations and prospective designs are needed to clarify the association between sarcoidosis and sarcopenia.